(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The collapse ofcentral authority led to the declaration of independence by the Subahdars of several provinces. Butall these states were primarily regional political entities interested inpromoting their own growth. They had no political or national outlook. Some ofthese states like Bengal, Hyderabad and Awadh–became for all practical purposesindependent owning a nominal allegiance to the Mughal Emperor. The Sikhs andthe Jats made successful bids for political power. The Marathas profited morethan any other people of India with the fall of the Mughal Empire. Theyestablished a mighty empire extending from the Punjab to Mysore.